A Study on the Development of Library ESG Management Evaluation Indicator and the Evaluation Result of Library ESG - Noh, Younghee (International Journal of Knowledge Content Development & Technology, 2024)
In this study, the library ESG evaluation indicators specialized for libraries were developed, and based on which, a survey was conducted targeting the actual libraries to evaluate the ESG level of libraries. As a result of the study, first, among the ESG evaluation indicators, the indicators of the social field and the governance field are demonstrating high in which field of the library's ESG evaluation indicators will appear the highest. The social area's high score of 3.70 seems to be because the protection of users' rights, occupational safety, and contribution to society and the local community are very closely related to the original role of the library. Second, it may be seen that there is a difference between the questions in the corporate governance part, while the averages are the same. In the case of library's cooperation, it turned out that it was 3.94 in the necessity evaluation of the evaluation indicators, but it was lowered to 3.61 in the actual library situation evaluation. Meanwhile, in connection with the activities of the director of library and the board of directors, it may be seen that the index evaluation increased from 3.32 to 3.58 in the actual evaluation.